Nurses’ Knowledge toward Bariatric Surgery at Surgical Wards at Teaching Hospitals in Al-Basra City - Ali Malik Tiryag; Hussein Hadi Atiyah (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to assess the level of nurses’ knowledge about bariatric surgery and to find the relationshipbetween Nurses’ knowledge about bariatric surgery and their demographic characteristics (age, gender, levelof education, and years of experience). A descriptive-analytic study was conducted on nurses’ knowledgetoward bariatric surgery at surgical wards at Al-Sader Teaching Hospital, Al-Faiha Teaching Hospital, andAl-Mawani Teaching Hospital in Al-Basra City. The period of the study was extended from the 15th ofNovember 2020 to the fifth of April 2021. Purposive (non-probability) sample covers (100) nurses whowork in the surgical wards, a questionnaire was designed to investigate nurses’ demographics, knowledgetoward obesity, bariatric surgery, complications of bariatric surgery, and postoperative nursing care andpatient education. The results of this study showed that 85% of studied nurses had poor knowledge aboutbariatric surgery, 14% of nurses had moderate knowledge and only 1% of nurses had good knowledge.